Assessment of knowledge, attitude and practice regarding hygiene among meat handlers in Vijayapura city, North Karnataka - Eariyaden, Fyroose; Yadavannavar, M. C.; Doddihal, Chandrika (International Journal Of Community Medicine And Public Health, 2024)
Background: Food-borne diseases are a significant health concern globally, particularly in meat-related cases, due to unhygienic handling and inadequate sanitation. Challenges such as inadequate food safety regulations, weak regulatory frameworks and insufficient awareness among food handlers contribute in exacerbating the issue. The aim of this study was to evaluate knowledge, attitudes, and practices of hygiene among slaughterhouse workers in Vijayapura, north Karnataka. Objective was to evaluate the sociodemographic characteristics of meat handlers and their correlation with knowledge, attitudes, and practices related to meat hygiene in in Vijayapura, north Karnataka. Methods: This descriptive, cross-sectional study was conducted in Vijayapura city from July to September 2023, involving meat handlers from various shops. 79 participants were selected from 200 shops using a lottery method, anticipating a 71% knowledge level of meat hygiene. Informed consent was taken, and data collection was done using a pretested, semi-structured questionnaire. Results: Among the 79 participants, 86.1% were male and 13.9% female, with 64.5% having over five years of experience. Most (96.2%) had good knowledge of meat hygiene, while 3.8% had poor knowledge. Significant associations were found between gender (p=0.00), religion (p=0.00), educational status (p=0.013), and meat hygiene practices. Conclusions: The study reveals satisfactory knowledge, attitudes, and practices regarding meat hygiene among meat handlers in Vijayapura. It is highly advisable to emphasize public health education, develop policies, and implement consistent training programs for meat handlers focused on safe meat handling practices, as well as maintaining high standards of personal and general hygiene.